STRATEGI PENGEMBANGAN KAWASAN PARIWISATA PANCUR AJI YANG BERDAYA SAING DAN BERWAWASAN LINGKUNGAN DI KABUPATEN SANGGAU - Ramadhan, Syahrul; Martoyo, Martoyo; Martinus, Martinus (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
This study aimed to discover the development strategy of a competitive and environmentally friendly tourism area which was located in Sanggau Regency, namely Pancur Aji Tourism. This research used a descriptive study with a qualitative approach. This study used Suwantoro Gamalâ€™s theory (1997) which consisted of attraction, tourism activity, accommodation, infrastructure, and institutional elements. The results showed that the tourism activity as the attraction and to impress the tourist was still inadequate, the development carried out was quite good in terms of tourist facilities and infrastructure as well as tourist service facilities but there was still no transportation service, and the infrastructure and institutional elements were quite good but still not optimal due to lack of access to the entrance of the tourist attractions and the cooperation between The Culture and Tourism Department of Sanggau Regency had not been maximized yet. The researcher suggests that The Culture and Tourism Department should strive for optimal development so that it can be realized and materialized that the Pancur Aji tourist attraction becomes better, can compete, and becomes superior.Â Keywords: Strategy, Development, Tourism